Regulation of Toll-Like Receptor (TLR) Signaling Pathway by Polyphenols in the Treatment of Age-Linked Neurodegenerative Diseases: Focus on TLR4 Signaling - Azam, Shofiul; Jakaria, Md.; Kim, In-Su; Kim, Joonsoo; Haque, Md. Ezazul; Choi, Dong-Kug (Frontiers in Immunology, 2019)
Neuronal dysfunction initiates several intracellular signalling cascades to release different proinflammatory cytokines and chemokines, as well as various reactive oxygen species. In addition to neurons, microglia and astrocytes are also affected by this signalling cascade. This release can either be helpful, neutral or detrimental for cell survival. Toll-like receptors (TLRs) activate and signal their downstream pathway to activate NF-κB and pro-IL-1β, both of which are responsible for neuroinflammation and linked to the pathogenesis of different age-related neurological conditions. However, herein, recent aspects of polyphenols in the treatment of neurodegenerative diseases are assessed, with a focus on TLR regulation by polyphenols. Different polyphenol classes, including flavonoids, phenolic acids, phenolic alcohols, stilbenes and lignans can potentially target TLR signalling in a distinct pathway. Further, some polyphenols can suppress overexpression of inflammatory mediators through TLR4/NF-κB/STAT signalling intervention, while others can reduce neuronal apoptosis via modulating the TLR4/MyD88/NF-κB-pathway in microglia/macrophages. Indeed, neurodegeneration aetiology is complex and yet to be completely understood, it may be that targeting TLRs could reveal a number of molecular and pharmacological aspects related to neurodegenerative diseases. Thus, activating TLR signalling modulation via natural resources could provide new therapeutic potentiality in the treatment of neurodegeneration.